2017
DOI: 10.1158/1535-7163.mct-17-0077
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TAO Kinases Using a New Inhibitor Compound Delays Mitosis and Induces Mitotic Cell Death in Centrosome Amplified Breast Cancer Cells

Abstract: Thousand-and-one amino acid kinases (TAOK) 1 and 2 are activated catalytically during mitosis and can contribute to mitotic cell rounding and spindle positioning. Here, we characterize a compound that inhibits TAOK1 and TAOK2 activity with IC values of 11 to 15 nmol/L, is ATP-competitive, and targets these kinases selectively. TAOK inhibition or depletion in centrosome-amplified SKBR3 or BT549 breast cancer cell models increases the mitotic population, the percentages of mitotic cells displaying amplified cent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 46 publications
5
42
0
Order By: Relevance
“…TAOKs modulate the dynamics and organization of several cytoskeleton components [ 29 , 30 , 31 ]. TAOKs are activated catalytically during mitosis and neuritogenesis [ 32 , 33 , 34 , 35 , 36 ]. By phosphorylation of microtubule-binding proteins including tau, TAOK1 induces microtubule instability by causing dissociation of tau from microtubules, which results in their disassembly [ 30 , 31 , 37 ] ( Figure 3 A).…”
Section: Signaling Pathways and Cellular Physiologies Regulate By mentioning
confidence: 99%
See 3 more Smart Citations
“…TAOKs modulate the dynamics and organization of several cytoskeleton components [ 29 , 30 , 31 ]. TAOKs are activated catalytically during mitosis and neuritogenesis [ 32 , 33 , 34 , 35 , 36 ]. By phosphorylation of microtubule-binding proteins including tau, TAOK1 induces microtubule instability by causing dissociation of tau from microtubules, which results in their disassembly [ 30 , 31 , 37 ] ( Figure 3 A).…”
Section: Signaling Pathways and Cellular Physiologies Regulate By mentioning
confidence: 99%
“…TAOK2 was found to increase the levels of acetylated α-tubulin when associated with microtubules and also to bind and phosphorylate α- and β-tubulin in vitro [ 29 ]. It was demonstrated that in mitotic cells, activated TAOK1 localizes to the cytoplasm while TAOK2 localizes to the centrosomes, and both TAOKs are required for spindle positioning and mitotic cell rounding [ 33 , 35 ]. Garg et al [ 38 ] further showed that TAOK1 and 2 bind and phosphorylate the atypical Rho family protein Rnd3 and elicit the translocation of Rnd3 from the plasma membrane to the cytosol, which contributes to spindle positioning, mitotic cell rounding, and cytokinesis ( Figure 3 A).…”
Section: Signaling Pathways and Cellular Physiologies Regulate By mentioning
confidence: 99%
See 2 more Smart Citations
“…TAOK1 and TAOK2 are catalytically activated during mitosis and can contribute to mitotic cell rounding and spindle positioning. A recent study showed that TAOK inhibition prolongs the duration of mitosis in breast cancer cells, increases mitotic cell death, and reduces the percentage of cells exiting mitosis [30]. Furthermore, genetic analyses identified a rare TAOK2 homozygous missense variant that causes a novel form of primary immunodeficiency [31].…”
Section: Plos Onementioning
confidence: 99%